2022
DOI: 10.1002/job.2625
|View full text |Cite
|
Sign up to set email alerts
|

Customer courtesy and service performance: The roles of self‐efficacy and social context

Abstract: While the impact of negative customer treatment on service employees and their organizations is often emphasized in both scholarship and the popular press, relatively little work has examined the effects of customer courtesy. We draw on the social cognitive theory to theorize that customer courtesy can enhance service performance via its positive effect on employee self-efficacy. Although getting customers to display courtesy may be outside an organization's direct control, we reason that management can amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…Because of this concern, they would be hesitant to try their luck at anything. According to Yoon et al (2022) who came to a similar conclusion and stated the same hypothesis, people's self-efficacy may be diminished in prosocial settings as a result of concern about receiving a negative appraisal. However, it is of the utmost importance to keep in mind that various studies have demonstrated differing degrees of connections between being generous and having anxiety resulting from receiving bad evaluations.…”
Section: Literature Reviewmentioning
confidence: 83%
“…Because of this concern, they would be hesitant to try their luck at anything. According to Yoon et al (2022) who came to a similar conclusion and stated the same hypothesis, people's self-efficacy may be diminished in prosocial settings as a result of concern about receiving a negative appraisal. However, it is of the utmost importance to keep in mind that various studies have demonstrated differing degrees of connections between being generous and having anxiety resulting from receiving bad evaluations.…”
Section: Literature Reviewmentioning
confidence: 83%
“…Being empathetic allows representatives to better understand their customers and provide a more satisfactory experience (Ioannidou & Vaya, 2008). Clear communication is essential for ensuring that customers understand information provided to them (Reddy & Gupta, 2020): being courteous and treating customers with respect and courtesy at all times, being polite, friendly, and professional in your interactions (Yoon et al, 2022). According to scholars, transparency is the cornerstone of trust, as is clear pricing (Hanna et al, 2019).…”
Section: Discussion and Analysismentioning
confidence: 99%
“…Consistent with previous studies (e.g. Hu and Liden, 2013; Hur et al , 2022; Yoon et al , 2022), we used a competence scale consisting of three items developed by Spreitzer (1995). This scale was originally derived from Jones’s (1986) self-efficacy scale.…”
Section: Methodsmentioning
confidence: 99%